Investigating the modulatory role of chronological and biological age on performance predictors in youth swimmers - McNarry, M. A.; Lester, L.; Brown, J.; Mackintosh, K. A. (Journal of Science in Sport and Exercise, 2020)
Purpose: The aim of this study was to determine the modulatory roles of biological maturity and age on the predictors of performance in youth swimmers and their stability over a six-month training cycle. Methods: In total, 28 swimmers (10 pre-pubertal [6 boys], 11.1 ± 1.8 years; 18 pubertal [8 boys], 15.2 ± 2.0 years old) and 26 untrained controls (15 pre-pubertal [10 boys], 9.7 ± 1.5 years; 11 pubertal [6 boys], 14.4 ± 0.5 years old) were recruited. At baseline, 3- and 6-months, participants completed an incremental ramp cycle test, isometric handgrip strength test and countermovement jumps, with speed assessed as a measure of performance in swimmers. Principle component analysis (PCA) identified factors that described youth swimmers` physical profile, with linear mixed models subsequently used to determine their interaction with age and maturity on performance. Results: Aerobic fitness and upper body strength were significantly higher in the trained participants, irrespective of maturity status or time-point. Four key factors were identified through PCA (anthropometrics; strength; aerobic capacity; aerobic rate), accounting for 90% of the between parameter variance. Age exerted a widespread influence on swimming performance predictors, influencing all four factors, whilst maturity only influenced the aerobic factors. The key age of divergence was 13 years. Conclusion: Overall, the present study found no evidence of a maturational threshold in the aerobic or strength-related response to training in youth. The influence of age on performance predictors suggests that utilising a single or select group of parameters to inform selection and/or talent identification throughout the dynamic processes of growth and maturation should be avoided.